Digital Payment Adoption and Business Performance of Retail SMEs: A Mediation–Moderation Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The study examines the impact of digital payment system use in retail small and medium-sized enterprises (SMEs) its effectiveness, with particular attention given to financial digital literacy as a moderator and operational efficiency as a mediator. The quantitative approach is applied to this study, in which a structured questionnaire related to retail SME stakeholders is used to collect considerable aspects in conditions of digital payment system use and organizational performance. The results of this research unequivocally affirm and demonstrate a robust association exists between the use of digital payment systems and company performance is further amplified through improvements in operational efficiency. Besides that, financial digital literacy is considered a significant and important aspect for gaining maximum benefits from digital payment methods should be used appropriately that is effective and efficient in maximizing the benefits and performance.